Highly Efficient Zinc Oxide Nanoparticles Catalyzed Green Synthesis of 1,5-Benzodiazepines under Solvent-Free Path - Zhao1, Yuhao; Yu2, Xuejie; Saini3, Manpreet; Ma4, Yanxu; K. Singh3, Rajesh (Asian Journal of Chemistry, 2014)
An efficient and simple environment-friendly method for the preparation of substituted 1,5-benzodiazepines as biologically interesting compounds under heterogenous catalyst is described. The one-pot multicomponent condensation of o-phenylene-diamine and substituted ketones catalyzed by zinc oxide nanoparticles (ZnO NPs) under microwave under solvent-free condition has been developed. The present protocol provides a green and improved pathway for the synthesis of 1,5-benzodiazepines in terms of excellent yields, short reaction times and reusability of catalyst.